Innocence, knowledge, and wonder what happened to the sense of wonder I felt as a child? - Osho. (b)
Looks to each person's last state of innocence - childhood - to recover the capacity to approach life with a sense of wonder and spontaneous joy, rather than with the cynicism and sense of hopelessness that afflict so many adults.
Keywords: Spiritual life; Spirituality; Wonder; Curiosity